Design of Universal Jig for Standardization and Efficiency of Frame Production Chopper Motorcycle - Halim, Dimas Ardiansyah; Murdiono, Mohamad Bimo; Suparno, Joko; Aziizudin, Achmad; Purnomo, Agung; S, Arbye; Yogiswara, Cahyo Wibi; Putra, Setya Drana Harry (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2025)
Chopper motorcycle frames had a fierce and macho impression on users. The frame was characterized by high handlebars, long front legs and a low seat. Chopper motorcycles were suitable for casual riding. Therefore, the Chopper frame must be specially designed or custom-made. Making the frame required a jig to maintain precision and dimensional accuracy in accordance with the original frame. Making a universal jig allowed craftsmen to make Chopper frames according to market demand without leaving the center balance on the frame. The jig manufacturing process included material selection, measurement, material cutting, machining, jig calibration, jig assembly, welding, checking and finishing. The welding process used argon TIG welding. The use of the jig shortened the frame manufacturing time by 2 times faster and minimizes wasted frame material due to dimensional errors.